Viscoelasticity of children and adolescent brains through MR elastography. (March 2021) - Ozkaya, Efe; Fabris, Gloria; Macruz, Fabiola; Suar, Zeynep M.; Abderezaei, Javid; Su, Bochao; Laksari, Kaveh; Wu, Lyndia; Camarillo, David B.; Pauly, Kim B.; Wintermark, Max; Kurt, Mehmet
Abstract: Magnetic Resonance Elastography (MRE) is an elasticity imaging technique that allows a safe, fast, and non-invasive evaluation of the mechanical properties of biological tissues in vivo . Since mechanical properties reflect a tissue's composition and arrangement, MRE is a powerful tool for the investigation of the microstructural changes that take place in the brain during childhood and adolescence. The goal of this study was to evaluate the viscoelastic properties of the brain in a population of healthy children and adolescents in order to identify potential age and sex dependencies. We hypothesize that because of myelination, age dependent changes in the mechanical properties of the brain will occur during childhood and adolescence. Our sample consisted of 26 healthy individuals (13 M, 13 F) with age that ranged from 7-17 years (mean: 11.9 years). We performed multifrequency MRE at 40, 60, and 80 Hz actuation frequencies to acquire the complex-valued shear modulus G  =  G ′ +  iG ″ with the fundamental MRE parameters being the storage modulus ( G ′), the loss modulus ( G ″), and the magnitude of complex-valued shear modulus (| G |). We fitted a springpot model to these frequency-dependent MRE parameters in order to obtain the parameter α, which is related to tissue's microstructure, and the elasticity parameter k, which was converted to a shear modulus parameter ( μ ) through viscosity ( η ). We observed no statistically significant variation in the parameter μ, but a significant increase of the microstructural parameter α of the white matter with increasing age ( p  < 0.05). Therefore, our MRE results suggest that subtle microstructural changes such as neural tissue's enhanced alignment and geometrical reorganization during childhood and adolescence could result in significant biomechanical changes. In line with previously reported MRE data for adults, we also report significantly higher shear modulus ( μ ) for female brains when compared to males ( p  < 0.05). The data presented here can serve as a clinical baseline in the analysis of the pediatric and adolescent brain's viscoelasticity over this age span, as well as extending our understanding of the biomechanics of brain development.